252. Joint Decisions: Optimal Duration of Chronic Suppressive Antibiotics in Adults with Prosthetic Joint Infections Who Underwent Debridement, Antibiotics, Irrigation, and Retention of Prostheses. (4th December 2021) - Lin, Aung; Jagtiani, Anil C
Abstract: Background: Hip and knee arthroplasties are associated with complications including prosthetic joint infections (PJI). Management ranges from explantation to debridement, antibiotics, irrigation, and retention of prostheses (DAIR). In DAIR, patients receive intravenous antibiotics followed by chronic suppressive antibiotics. Current guidelines on suppressive antibiotic use after DAIR are unclear and based on expert consensus. This study seeks to elucidate the optimal duration of chronic suppressive antibiotics after DAIR. Methods: This is a retrospective cohort study of adults in the Southern California Kaiser Permanente System with hip and knee prosthetic joint infections who underwent DAIR from 2007-2017. Culture data and durations of suppressive antibiotics were collected and patients were followed for 1 year after completion. Treatment failure was determined by mortality, re-infection, or prosthesis removal. Patients who received no antibiotics vs. less than 3 months vs 3 to 6 months vs greater than 1 year were compared. Results: 350 charts were reviewed and 145 patients were included. There were 87 knee and 58 hip PJIs with 32 patients (22%) who failed treatment. There were more cases of failure when patients didn't receive suppressive antibiotics (27%) vs those who received any (19%), however the results were not significant. There were no significant differences in failure rates between short vs longer suppressive antibiotic courses regardless of the duration (Staph vs non-Staph, hip vs knee). Patients with Staphyloccocal infections and knee infections were significantly more likely to fail treatment (p=0.0196 & 0.0150, logistic regression). Conclusion: This study shows the importance of suppression with oral antibiotics after PJIs are treated with DAIR. The lack of difference in treatment failure between the durations of suppressive antibiotics makes it prudent to consider shorter courses of antibiotics, while placing attention on patients with knee and Staphylococcal infections as they are more likely to fail treatment. Limitations include sample size, difficulty in quantifying extent of initial infection and debridement, and provider dependent prolonging of antibiotic duration. Disclosures: All Authors : No reported disclosures